Short-course radiotherapy versus long-course chemoradiotherapy in total neoadjuvant therapy of rectal cancer – A multicenter analysis of early outcomes and toxicity - Wurschi, Georg; Kesselmeier, Miriam; Schneider, Melanie; Becker, Jan Niklas; Frerker, Bernd; Vorbach, Samuel M.; Ehret, Felix; Diefenhardt, Markus; Schunn, Fabian; von Gruben, Maria Elena; Büttner, Marcel; Hoffmann, Elgin; et al. (Radiotherapy and Oncology, 2025)
Background and Purpose: Total neoadjuvant therapy (TNT) improves local control and complete response (CR) rates in locally advanced rectal cancer (LARC). CR is associated with favorable local tumor control, allowing non-operative management (NOM). However, it remains unclear whether short-course radiotherapy (SCRT) or long-course chemoradiotherapy (LCRT) is preferable within TNT. Methods: LARC patients undergoing TNT between 2015 and 2024 were included in this retrospective multicenter analysis (DRKS00033000). The primary endpoint was CR. Secondary endpoints comprised NOM rates, toxicity, and tumor control. Multivariable logistic regression modelling was used to assess the influence of LCRT. Results: Of 295 included patients with a median age at diagnosis of 62 (Q1-Q3: 54–68) years and 210 (71.2 %) men, 172 (58.3 %) underwent LCRT. CR was achieved in 46 (37.4 %) SCRT and 96 (55.8 %) LCRT patients. Acute toxicity grade ≥ 3 occurred in 24 (20.5 %) of 117 SCRT and in 62 (36.3 %) of 171 LCRT patients. Within a median follow-up of 19.4 months (SCRT) and 19.6 months (LCRT), 23 (19.8 %) of 116 and 30 (19.4 %) of 155 patients experienced recurrence, respectively. Regression modelling revealed an increased likelihood for CR (adjusted odds ratio: 3.11; 95 % confidence interval: 1.37–7.07) and NOM (4.40; 1.46–13.21) with LCRT, whereas no significant associations of LCRT with acute toxicity (0.90; 0.40–2.02), chronic toxicity (1.16; 0.48–2.78), postoperative complications (0.89; 0.62–1.28) or recurrence (0.81; 0.31–2.16) were observed. Conclusion: LCRT was associated with higher CR and NOM rates. Whether it might be preferred over SCRT for intended NOM remains a relevant question to be answered by ongoing randomized trials.
CRIS-Team Scopus Importer:2025-10-31
Keywords: Chemoradiotherapy; Complete response; Rectal cancer; Total neoadjuvant therapy